The Armenian Issue in 1912-1914 and the Extra-Parliamentary Activities of the Armenian Deputies of the Ottoman Parliament - Martirosyan, Narek (History and Culture, 2022)
Armenian MPs of the Ottoman Parliament made a contribution to the discussion of the Armenian Question by the Great Powers in 1912-1914. The Armenian MPs, on the one hand, undertook, in the structure of the commission, to develop a plan for reforms in Western Armenia and duly present it to the Great Powers, and on the other hand, undertook such a difficult and dangerous task as the negotiations with the authorities of Young Turks. Young Turks, on the contrary, did everything to obstruct the negotiation process and thereby prevent reforms. Armenian MPs since 1913 stopped meetings with Young Turks so as not to interfere with the negotiation process. Soon, on January 26, 1914 there was signed an agreement between Russia and the Ottoman Empire on the implementation of reforms in Western Armenia. On the initiative of the Armenian MPs, contacts with the European inspectors Hoff and Vestenenk were established. In May of 1914, Talaat Pasha signed an agreement with the European inspectors, according to which real power in Western Armenia passed from inspectors to the hands of the Young Turks. The Young Turks, dissatisfied with even this modest agreement, in June of 1914, demanded from the inspectors to leave the Ottoman Empire.